PROGRAM IMPLEMENTATION AND COMPETENCE OF STUDENTS OF TECHNICAL VOCATIONAL AND LIVELIHOOD (TVL) TRACK - Loriene Yrac Garra (Faculty of Business, President University, 2023)
This study was conducted to determine the extent of TVL program implementation and the level of competence of Grade 12 students in the province of Capiz. A mixed-method research design employing quantitative and qualitative approaches in gathering data was used. A random sample of 754 Grade 12 TVL students from public and private schools was chosen as respondents of the study. For quantitative, the researcher utilized a descriptive-correlational. Proportionate random sampling was employed to determine the number of respondents per school. A researcher-made questionnaire and in-depth interviews were used to gather the data. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, f-test, Analysis of Variance, and Pearson-r. For qualitative, an in-depth interview was conducted. The study revealed that the extent of TVL program implementation in the province of Capiz was high as a whole and in terms of teacher and instruction, facility and equipment, and work immersion preparedness. Also, the level of competence of Grade 12 students as a whole and in terms of knowledge, skills, and attitude was high. There were no significant differences found in the extent of TVL program implementation and the level of competence of Grade 12 students when grouped according to their selected profiles. Lastly, there was a significant relationship between the extent of TVL program implementation and the level of competence of Grade 12 students in the province of Capiz.